Low Noise Amplifier For Medradio Application - Segaran, Abbiramavali (Universiti Sains Malaysia, 2018)
This work presents the design and simulation of a low power LNA for MedRadio band using the standard 0.18 μm CMOS process technology. This inductor-less LNA is implemented with resistive shunt feedback circuit technique with an output buffer. For medical device that is being implanted in human body, the power consumption is one of the domain concern in order to ensure it last longer in the human body. With low power consumption, this LNA could ensure longer battery life for the implementation of medical devices that are implanted into human body. The design and simulation were done via Cadence IC5 with Silterra’s 0.18 μm CMOS technology. It is obtained that the power consumption of this LNA is just 1mW due to the resistive shunt feedback network. The design (on simulation) operates at low power consumption with gain of 11.6 dB, NF of 7.5 dB and input return loss of 10.1 dB between 401 MHz to 406 MHz MedRadio band.